Determinan Biologi Maternal Dan Sosial Ekonomi Apakah Yang Berhubungan Dengan Persalinan Tindakan SC Pada Ibu Bersalin Di RSU Wiradadi Husada - Riyanto, Refni (Universitas Muhammadiyah Semarang, 2015)
Maternal Biological And Socio-Economic Determinants Are Associated With Delivery of SC Actions in Maternal Maternity at Wiradadi Husada General Hospital Background: Prevalence of maternal mortality in Indonesia on 2010 was 228/100.000 live births. Childbirth complication was a risk factor of prevalence of maternal mortality. Number of childbirth complication was estimated 31%. Theincidence of complications of childbirth labor requires action to improve maternal morbidity . However , delivery to the action has the risk of maternal morbidity and mortality is higher than the persalianan without action or normal delivery . The high number of deliveries through the action section is Cesaria ( SC ) in Wiradadi Husada Hospital due to several factors including maternal factors biological and socio-economic factors that accompany the birth mothers. Objective: The objective of the study to identified determinant of maternal biology ang economic social whether related to childbirth sectio caesarea action on women giving birth in public hospitals Wiradadi Husada Method: The study was an analitic observational study using case control design. The population of the study was 144 subjects, consists of two groups, namely case group and control group, with 1:1 comparison. Sampling method using purposive sampling. Data was a secondrary data and was collected by observation sheet. Data analysis using univariat analysis, bivariat analysis through pearson chi square and multivariat analysis. Result: There are three maternal biological factors related to labor actions in RSU Wiradadi SC Husada ie maternal age (p value 0.002 <0.05) , nutritional status (p value 0.024 < 0.05) , and a history of birth complications (p value 0,000 <0 , 05). There are two socio-economic factors associated with labor action in RSU Wiradadi SC Husada, namely economic status (p value 0.03 <0.05) and geographic groups (p value 0.012 <0.05). Conclussion: Based on the results of the study showed that variables history of birth complications are the most dominant veriabel related to childbirth sectio caesarea action on women giving birth in Public Hospitals Wiradadi Husada.